Isolation and characterization of the LGT1 gene encoding a low-affinity glucose transporter from Torulaspora delbrueckii - Araújo, Cecília Alves (2005)
Torulaspora delbrueckii PYCC 5321 displayed a mediated glucose transport activity best fitted assuming a biphasic Michaelis-Menten kinetics with a low- and a high-affinity component. A genomic library of this yeast strain was used to transform a mutant of Saccharomyces cerevisiae deficient in glucose transport. Sequence analysis of a DNA fragment cloned, revealed the presence of a 1,704 bp-length ORF. This ORF, named LGT1, displayed a high homology to yeast glucose transporter genes. Functional characterization of the LGT1 gene product in S. cerevisiae revealed that it encodes a low-affinity transporter, able to mediate the uptake of glucose and fructose. In consonance with this, expression of LGT1 in S. cerevisiae was high in media containing 4% of glucose and almost undetectable in galactose as sole carbon source. In the absence of glucose, repression of LGT1 expression required the transcription factor Rgt1p. However, a functional Rgt1p does not appear to be required for a full induction of LGT1 at high glucose levels. Deletion of the gene coding for the general repressor Mig1p had no effect on LGT1 expression, but additional disruption of MIG2 in a mig1 background indicated that Mig2p or both Mig1p and Mig2p in a redundant way, act as repressors of LGT1 expression at high glucose concentrations. The GeneBank Accession No. for LGT1 is AY598344.